Democratizando as relações de trabalho: a experiência de dirigentes sindicais nas mesas de negociação permanente do SUS - Ferreira Júnior, José Inácio (2023)
The Permanent Negotiation Tables of SUS (Mesas de Negociação Permanente do SUS - MNP-SUS) were conceived as a decision-making instance of the SUS that incorporates collective labor negotiation as part of a work management policy, inaugurating a new stage of relations between the union movement of public servants and the State as an employer. Focusing our study on some MNP-SUS in the states of Minas Gerais-MG and Ceará-CE, we conducted interviews with 08 union leaders who acted as negotiators in this space in order to understand how their participation in the negotiation process influenced the dynamics of the union entity's performance that represent. In order to understand how the union action developed from this participation, we used the contributions of Political Psychology and specifically used Salvador Sandoval's Study Model of Political Consciousness. As a result, we identified that the MNP-SUS acted in a complementary way in the intersection between the decision-making instances of the SUS and although the dimension of the construction of a work management policy has enabled the development of a cooperative and constructive relationship, the treatment that public managers give to collective bargaining in the public sector and the wear and tear that result from it have meant that the more conflictive nature of this dimension has been superimposed and reduced its potential to be used as a management tool. Maintaining a posture of neglect and even blockage of collective bargaining that was adopted by public managers throughout history has always been the object of attention of union leaders and, as a result of this, the union action observed in this research reveals that their performance in the The table was guided by the search for strengthening this forum and the commitment to its constructive development, but always remaining alert and prepared for a rupture, which is typical of the limits of collective bargaining itself as a space for conflict resolution, but also as a reaction to the attitude of managers in relation to collective bargaining